Nutrition knowledge, attitudes and practices of primary school learners’ parents in Mkoba South: implications for nutrition education. - Mapiwa, Sefa Ellen (Midlands State University, 2020)
The main purpose of this study was to assess the nutrition knowledge, attitudes and practices within the Mkoba South community and promote nutrition education with the aim of improving nutrition knowledge and food choices, to encourage a better quality of life and improve performance of learners. The research was qualitative in nature and the design used was the participatory action research. Due to the nature of the research design adopted, a purposive sample was drawn from the population and comprised of 10 participants. For the purposes of this study, focus groups, food frequency questionnaires, and observation were the methods for data collection. The major findings were that the constraints of low income construct practical barriers to healthy eating, further socio-environmental factors, such as culture, lack of literacy and education, enhance the effects of deficiency in nutritional knowledge, negative attitudes and poor practices. The major conclusion reached was that there is definite need for Nutrition Education to be implemented for the benefit of the learners in primary schools.